ANALYSIS OF OIL CONTENT AND DIATOMS ABUNDANCE IN SIMBUR NAIK WATERS, TANJUNG JABUNG TIMUR REGENCY JAMBI ISLAND PROVINCE - Ilham Ilham; Bintal Amin; Joko Samiaji (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract The research was conducted in August2018 with the aim to analyze the total oil content,determined type and abundance of diatoms, also determined the correlation between oil content and abundance of diatoms in the waters of Simbur Naik village, Jambi Province. The method is used in this research wasSurvey method consisted of four stations with three repetitions. The average value of oil content ranged between 0,0529 –0,7289 ppmand the abundance of diatoms were between 138,33 ind/ℓ - 417 ind/ℓ.The diatoms which consist of 15 speciesChaetocerossp, Fragilariasp,Surirellasp, Gyrosigmasp, Cymbellasp, Coscinodiscussp, Isthimiasp, Prorocentrumsp, Diploneissp, Nitzschiasp, Synedrasp, Rhizosoleniasp, Thalasssionemasp, Leptocylindrussp, andAulacoseriagranulata. The coralations between total oil content and the abudance of diatoms have a weak negatife relationship which meant the oil content does not significantly effect the abudance of diatoms. The regression equation was y = 300,1+ 60,78x and the coefficient correlation (R2 = 0,014);(r) = 0,118.Keywords: Abundance, diatoms, oil contenc, Jambi.